Social Isolation Stress in Adolescence, but not Adulthood, Produces Hypersocial Behavior in Adult Male and Female C57BL/6J Mice - Rivera-Irizarry, Jean K.; Skelly, Mary Jane; Pleil, Kristen E. (Frontiers in Behavioral Neuroscience, 2020)
Chronic stress during the developmental period of adolescence increases susceptibility to many neuropsychiatric diseases in adulthood, including anxiety, affective, and alcohol/substance use disorders. Preclinical rodent models of adolescent stress have produced varying results that are species, strain, sex, and laboratory-dependent. However, adolescent social isolation is a potent stressor in humans that has been reliably modeled in male rats, increasing adult anxiety-like and alcohol drinking behaviors, among others. In this study, we examined the generalizability and sex-dependence of this model in C57BL/6J mice, the most commonly used rodent strain in neuroscience research. We also performed a parallel study using social isolation in adulthood to understand the impact of adult social isolation on basal behavioral phenotypes. We found that six weeks of social isolation with minimal handling in adolescence through early adulthood (postnatal day (PD) 28 to 70) produced a hypersocial phenotype in both male and female mice and an anxiolytic phenotype in the elevated plus maze in female mice. However, it had no effects in other assays for avoidance behavior or on fear conditioning, alcohol drinking, reward or aversion sensitivity, or novel object exploration in either sex. In contrast, six weeks of social isolation in adulthood beginning at PD77 produced an anxiogenic phenotype in the light/dark box but had no effects on any other assays. Altogether, our results suggest that 1) adolescence is a critical period for social stress in C57BL/6J mice, producing aberrant social behavior in a sex-independent manner and 2) chronic individual housing in adulthood does not alter basal behavioral phenotypes that may confound interpretation of behavior following other laboratory manipulations.